THE MEDIATING ROLE OF BRAND IMAGE AND BRAND LOYALTY IN THE INFLUENCE OF SUSTAINABLE MARKETING ON CONSUMER SUSTAINABLE PURCHASES AT THE BODY SHOP MALANG - Didik Priyo Sugiharto (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the mediating role of Brand Image and Brand Loyalty in the influence of Sustainable Marketing on Sustainable Purchasing among The Body Shop consumers.Methods: this study is a quantitative approach with a causality research design to test the relationship between variables. Data were collected through distributing questionnaires to respondents determined using a purposive sampling technique with the criteria of consumers who have purchased The Body Shop products. The collected data were then analyzed using path analysis techniques to test hypotheses regarding the direct and indirect effects between research variables. The results of the analysis show that Sustainable Marketing has a significant effect on Brand Image and Brand Loyalty, while Brand Loyalty is proven to play a full mediator in encouraging Sustainable Purchasing.Results: The results of the analysis show that Sustainable Marketing has a significant effect on Brand Image and Brand Loyalty, while Brand Loyalty is proven to play a full mediator in encouraging Sustainable Purchasing. This study contributes to the development of marketing science by emphasizing that effective sustainable strategies must be able to go beyond the cognitive aspect and touch the affective dimension of consumers to create lasting purchasing behavior. The research gap of this study lies in the focus on strengthening the affective dimension through emotional attachment as the main mediator, which is different from previous studies that emphasize more on cognitive perception of brand image or less consider the role of emotional loyalty specifically in the context of established brands, in addition to the inconsistency of previous research findings regarding the dominance of cognitive versus affective factors in mediating sustainable marketing relationships and sustainable consumer purchases. Keywords: Brand Image, Brand Loyalty, Sustainable Marketing, Sustainable Purchasing